DPOAE measurements in factory workers with cochlear hearing loss - Szczepaniak, O.; Błaszak, M.A. (Archives of Acoustics, 2006)
The main aim of the study was to find a correlation between the pure-tone threshold measuredby a classic audiometer and estimated from input/output function of distortion productotoacoustic emission. The measurements were performed for a group of 27 factory workersand a control group of 10 young subjects with normal hearing (YNH). The interrelations betweenthe results of these two methods were analyzed with respect to all measured frequenciesand for six groups of subjects representing different characteristics of audiograms. The UCL(uncomfortable level) influence on I/O-functions was also considered.